Hyacinth and River Grass Utilization for Production Methanol and Hydrogen as Fuel - Harsha J. Abhichandani, Neha S. Deshmukh, Amruta A. Chavan, Ranjitsing P. Gaikwad (Mathematical Statistician and Engineering Applications, 2022)
Sustainable Environment Development includes use of Biomass such as Hysinth and river grass to produce Methanol and Hydrogen Liquid. The Hysinth and river grass to methanol and hydrogen liquid synthesis is crucial in renewable industry for fuel. The Hysinth and river grass Gasification is useful to produce methanol as well as further hydrogen gas shall be developed with separate process. The objective is to perform design parameters to produce Hysynth to methanol and hydrogen gas from a syngas by use of hysinth and river grass biomass gasification process. Biomass gasification includes syngas compression at 80 bar, this is considered as optimum pressure for methanol production. The objective is also to review and make utilization of Hysinth and River grass in rivers for production of methanol fuel as well as hydrogen fuel in India.